The Alternative Pathway Is Necessary and Sufficient for Complement Activation by Anti-THSD7A Autoantibodies, Which Are Predominantly IgG4 in Membranous Nephropathy - Manral, Pallavi; Caza, Tiffany N.; Storey, Aaron J.; Beck, Laurence H.; Borza, Dorin-Bogdan (Frontiers in Immunology, 2022)
Membranous nephropathy (MN) is an immune kidney disease characterized by glomerular subepithelial immune complexes (ICs) containing antigen, IgG, and products of complement activation. Whereas proteinuria is caused by complement-mediated podocyte injury, the pathways of complement activation remain controversial due to the predominance of IgG4 in ICs, an IgG subclass considered unable to activate complement. THSD7A, a transmembrane protein expressed on podocytes, is the target autoantigen in 3% of cases of primary MN. In this study, we analyzed sera from 16 patients with THSD7A-associated MN with regard to the anti-THSD7A IgG subclasses and their ability to fix complement in vitro. The serum concentration of anti-THSD7A IgG varied over two orders of magnitude (1.3-243 μg/mL). As a relative proportion of all IgG anti-THSD7A, IgG4 was by far the most abundant subclass (median 79%), followed by IgG1 (median 11%). IgG4 was the dominant subclass of anti-THSD7A antibodies in 14 sera, while IgG1 was dominant in one and co-dominant in another. One quarter of MN sera additionally contained low levels of anti-THSD7A IgA1. ICs formed by predominantly IgG4 anti-THSD7A autoantibodies with immobilized THSD7A were relatively weak activators of complement in vitro, compared to human IgG1 and IgG3 mAbs used as positive control. Complement deposition on THSD7A ICs was proportional to the amount of anti-THSD7A IgG and occurred to a significant extent only at relatively high concentration of anti-THSD7A IgG (above 3 μg/mL in our assay). C3b fixation by THSD7A ICs was completely abolished in factor B-depleted sera, partially inhibited in C4-depleted sera, and unchanged in C1q-depleted sera. These results imply that THSD7A ICs predominantly containing IgG4 activate complement at high IgG4 density, which strictly requires a functional alternative pathway. These findings advance our understanding of how IgG4 antibodies activate complement.